2016
DOI: 10.1080/0267257x.2016.1170720
|View full text |Cite
|
Sign up to set email alerts
|

Brand identity and online self-customisation usefulness perception

Abstract: Online self-customisation (OSC) enables customers to tailor their preferences to certain product features via a brand-hosted online platform. Recent literature has given increasing attention to how consumers value OSC. However, extant research is characterised by a scarcity of understanding the effects of brand identity and individual differences on consumer responses to OSC. The purpose of this paper is to examine the mediating role of trust and the moderating role of need for uniqueness on the effects of bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 103 publications
(128 reference statements)
0
24
0
1
Order By: Relevance
“…De la Cuesta-Benjumea (2011) describes that the acts and objects exist and have meaning because those can be described through words, fact that the entrepreneurs did by generated a symbolic value for each word assigned to the service provided by the company. This implies that the brand provides a self-expression of identity, which is the capacity to consider oneself as an object and in that process constructing a narrative on the organization (He, Harris, Wang and Haider, 2016). Obtained results by comparing Pearson and Spearman's Rho correlations point out that there is no association between time on market for the studied companies and Aaker's (1997) desired brand personality model.…”
Section: Research Resultsmentioning
confidence: 92%
“…De la Cuesta-Benjumea (2011) describes that the acts and objects exist and have meaning because those can be described through words, fact that the entrepreneurs did by generated a symbolic value for each word assigned to the service provided by the company. This implies that the brand provides a self-expression of identity, which is the capacity to consider oneself as an object and in that process constructing a narrative on the organization (He, Harris, Wang and Haider, 2016). Obtained results by comparing Pearson and Spearman's Rho correlations point out that there is no association between time on market for the studied companies and Aaker's (1997) desired brand personality model.…”
Section: Research Resultsmentioning
confidence: 92%
“…Since self-designed products provide a higher preference fit than standardized products and thus drive customers’ willingness to pay ( Franke and Piller, 2004 ; He et al, 2016 ), such a special co-creation activity may induce affective reactions and thus increase the value the customer attaches to the product. Previous self-designed research in the co-creation literature also concluded that such premium could be attributed not only to the superior fit with preferences that customized products provide ( Franke and Piller, 2004 ; Franke et al, 2009 ; He et al, 2016 ), but also to the sense of accomplishment (the “I Designed it Myself” effect) and ownership ( Wiecek et al, 2019 ) consumers feel when they successfully complete the design process ( Moreau and Herd, 2010 ). Therefore, in this research, we focus on self-design activities as our research context and define the self-design activities as a strategy that firms use to give customers a chance to actively engage in the creation of end products, allowing them to select or create the final products for themselves with the company providing production and delivery.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Once selected, the customized design becomes a real Lego set that can be purchased around the world with royalties paid to the set’s creator. No wonder recent research has demonstrated that consumers are willing to pay a significant premium for self-design or customized products relative to comparable mass-produced counterparts ( Franke and Piller, 2004 ; Franke et al, 2009 ; He et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Tüketicilerin, algılanan marka kimliği ile kendi kişisel veya sosyal kimliğiyle uyuştuğu bir markayı seçme ihtimali daha yüksektir. 12 Marka kimliği ise, bir markanın ayırt edici ve nispeten kalıcı özelliklerini belirtir. 13 Bununla birlikte sosyal kimlik perspektifi, marka kimliğini (brand identity), marka özdeşleşmesinin öncüsü olarak belirtir.…”
Section: Tüketici -Marka öZdeşleşmesiunclassified